Evaluating musculoskeletal imaging communication interventions using behavioural science: a scoping review using the COM-B model - Andrew Bateman; Edward Kirby; Andrew MacMillan; Andrew Brinkley; Bernard X W Liew (BMJ Open)
Objectives Clinicians and patients have been found to attribute musculoskeletal (MSK) pain to normal age-related changes seen on imaging, which can negatively impact patient outcomes and increase healthcare costs. While some studies have tested interventions to improve how MSK imaging findings are communicated, their impact has been limited. Applying a behavioural science framework has the potential to identify the rationale and target of these interventions to inform future intervention design—an analysis that has not yet been conducted. This study aims to identify the Behaviour Change Techniques (BCTs), the behavioural targets and the theoretical basis of interventions seeking to affect the communication of MSK imaging.Design Scoping review using the Capability, Opportunity, Motivation - Behaviour (COM-B) model.Data sources Searches of MEDLINE, EMBASE, CINAHL, AMED and PsycINFO from inception to 9 February 2024.Eligibility criteria for selecting studies We included studies that have developed or evaluated interventions which target the communication of MSK imaging findings. Interventions targeting both patients and clinicians were included. Experimental and quasi-experimental study designs were included, and studies that focused on serious or specific known causes of MSK pain were excluded.Data extraction and synthesis Two independent authors extracted study participant data and intervention details. A theory of behaviour called the COM-B model was used to map the BCTs and behavioural components targeted by studies.Results We identified 11 studies from 2486 studies in our electronic search. 11 different BCTs were identified across 11 studies. The most common techniques were framing/reframing (nine studies), adding objects to the environment (eight studies), incompatible beliefs (seven studies) and avoidance/reducing exposure to cues for the behaviour (four studies). Only two studies (feasibility studies) used behavioural theory to guide their intervention design. While one study showed a large effect, most interventions had little to no impact on pain, disability, or fear over time.Conclusion This review highlighted a lack of studies targeting clinician knowledge and the provision of high-quality patient resources about the nature of MSK pain, even though the broader literature identifies both as enablers of effective health communication. Additionally, the absence of a theory-informed design likely resulted in attempts to reassure patients about normal age-related imaging findings without providing an alternate, more coherent explanation for symptoms. Future interventions should focus on enhancing clinician psychological capability (knowledge) as well as clinician and patient reflective motivation (beliefs) to enable more helpful explanations of MSK symptoms. The key challenge for future interventions will be achieving these aims in a way that is effective, consistent and practical.Trial registration details Open Science Framework (https://doi.org/10.17605/OSF.IO/ECYS8).